Levels of reading comprehension in high school students. A comparison by topic - Guevara Benítez, Yolanda (2015)
Under the theoretical basis of the interbehavioral psychology, were developed and validated two tests to assess reading comprehension of texts related with two topics: one literary and one of biology, in three functional levels. The aim was to analyze the performance of junior high school students, in reading comprehension. Participants were 90 students enrolled in the first grade of three school groups from a public school. The results show that students achieved low percentages of correct answers in both tests, in particular, their worst performance was related with the topic of biology. The results of the students were classified in three ranges of performance. The advantages of evaluating reading comprehension considering the functional levels of behavior and topic, are discussed.